2021
DOI: 10.3390/life11121317
|View full text |Cite
|
Sign up to set email alerts
|

Using Telemedicine to Provide Education for the Symptomatic Patient with Chronic Respiratory Disease

Abstract: Technology-enabled learning, using computers, smartphones, and tablets, to educate patients on their respiratory disease and management has grown over the last decade. This shift has been accelerated by the global COVID-19 pandemic and the need to socially distance for public health. Thirteen recently published papers examined experience, knowledge, skills and attitude acquisition, behaviour change, and impact on health outcomes of patient education using technology (websites and mobile device applications) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Whereas the other COPD apps appear to provide combinations of didactic education, symptoms tracking, exercise encouragement and collaborations with clinicians (Bentley et al 2020 ; Crooks et al 2020 ; Farmer et al 2017 ; Kwon et al 2018 ; North et al 2020 ; Park et al 2020 ; Vorrink et al 2016 , 2017 ; Wang et al 2021b ). Two key components that appear frequently across these apps are the interactive feedback and the possibility to collaborate with their healthcare teams, features well suited to optimize acceptability and implementation among patients (Blackstock and Roberts 2021 ; Morrison et al 2016 ; Wang et al 2021a ). However, the apps in these RCTs may have the potential to provide additional designs or features not discussed here as this study was limited to synthesizing the information that was inconsistently reported across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the other COPD apps appear to provide combinations of didactic education, symptoms tracking, exercise encouragement and collaborations with clinicians (Bentley et al 2020 ; Crooks et al 2020 ; Farmer et al 2017 ; Kwon et al 2018 ; North et al 2020 ; Park et al 2020 ; Vorrink et al 2016 , 2017 ; Wang et al 2021b ). Two key components that appear frequently across these apps are the interactive feedback and the possibility to collaborate with their healthcare teams, features well suited to optimize acceptability and implementation among patients (Blackstock and Roberts 2021 ; Morrison et al 2016 ; Wang et al 2021a ). However, the apps in these RCTs may have the potential to provide additional designs or features not discussed here as this study was limited to synthesizing the information that was inconsistently reported across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Technologically enabled learning is a growing field for patient (and clinician) education with the use of computers, smartphones, tablets, and mobile applications. Moreover, technological support can effectively promote patient self-care, medication adherence, and physical activity among those with chronic respiratory conditions [67]. With the increased use of telemedicine, digital interventions need to align with clinical guidance, be context-relevant relevant and appropriately reviewed for quality and impact [67].…”
Section: Technological Interventionsmentioning
confidence: 99%
“…Moreover, technological support can effectively promote patient self-care, medication adherence, and physical activity among those with chronic respiratory conditions [67]. With the increased use of telemedicine, digital interventions need to align with clinical guidance, be context-relevant relevant and appropriately reviewed for quality and impact [67]. The use of telehealth and digital solutions has been utilised across the GACD grant recipients and remains on the agenda as a priority in further funding rounds.…”
Section: Technological Interventionsmentioning
confidence: 99%
“…Apart from traditional video conferences and phone calls to communicate with providers, telemonitoring combined with plentiful modern technologies has attracted more attention than usual during the pandemic ( 43 ). Wearable technology that can monitor physical activity, blood pressure, and other information has gained traction, allowing real-time synchronous and asynchronous data and biodata to be delivered to healthcare providers to provide more personalized and precise decisions for patients with chronic diseases ( 44 , 45 ).…”
Section: Acceleration Of Telehealth Development During the Covid-19 O...mentioning
confidence: 99%